A Solution of the Keynes-Hicks-Hansen Non-Linear Employment Model - Brems, Hans (Quarterly Journal of Economics, 1956)
I. Goods and money, 303. — II. The variables of the model, 304. — III. The real-sphere behavior equations, 305. — IV. The money-sphere behavior equations, 306. — V. Two equilibrium conditions, 308. — VI. A politically given parameter, 308. — VII. Solution, 309. — VIII. The sensitivity of national output to changes in the parameters, 310. — IX. Conclusion, 312.